2018
DOI: 10.21037/jtd.2018.03.41
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of soluble triggering receptor expressed on myeloid cells-1 in mice with Acinetobacter baumannii colonization and infection in the lung

Abstract: Background: Acinetobacter baumannii (A. baumannii) is one of the most troublesome opportunistic pathogens associated with hospital-acquired pneumonia (HAP). It is important to be able to discriminate A. baumannii colonization from infection in its early stages so that effective antibiotics can be promptly applied.Recent studies have reported that the secretion of soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) is markedly upregulated in pneumonia and sepsis, but the expression pattern of sTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Microbial culture, WBC count and classification, CRP, PCT, and temperature monitoring are used to distinguish infection from colonization. A new inflammatory marker, sTREM-1 ( 8 , 16 , 26 , 27 ), for identifying bacterial infection and colonization in experimental animals has recently been reported ( 2 ). The current study found sTREM-1 and PCT to be significantly higher in the infection relative to the colonization group on days 1 to 10 ( P < 0.05), demonstrating the potential utility of these two biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Microbial culture, WBC count and classification, CRP, PCT, and temperature monitoring are used to distinguish infection from colonization. A new inflammatory marker, sTREM-1 ( 8 , 16 , 26 , 27 ), for identifying bacterial infection and colonization in experimental animals has recently been reported ( 2 ). The current study found sTREM-1 and PCT to be significantly higher in the infection relative to the colonization group on days 1 to 10 ( P < 0.05), demonstrating the potential utility of these two biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…All data were tested for normality and normally distributed data are expressed as mean ± standard deviation with differences between two independent samples tested by t test ( 2 ). Nonnormally distributed data are expressed as median (quartiles) (M [QL–QU]) and were tested using Mann-Whitney U test ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations